Examining Memorable Tourism Experience On Memorable Trip Experience, Subjective Well-Being And Revisit Intention - B. MONIKA,; THAMARAISELVAN, DR. N.; SIVANESAN, DR. G. (The journal of contemporary issues in business and government, 2021)
The present study examined the memorable tourism experience of Kim et al (2012) dimension on memorable tripe experience, subjective well-being and revisit intention. The data were collected from 362 respondents through online among the tourist in Pondicherry, India. Structural equation modeling was adopted to test the hypotheses developed for the study. The result shown the subjective well-being acted as mediating dimension between memorable trip experience and revisit intention. All the four hypotheses developed for the study were accepted.